Toward an Integrated Multilevel Theory of Crime at Place: Routine Activities, Social Disorganization, and The Law of Crime Concentration - Jones, Roderick W. (Journal of quantitative criminology, 2019)
We propose and test a multilevel theoretical model of crime concentration by combining criminal opportunity and social disorganization into a single hierarchical model. Our theoretical model simultaneously answers calls to integrate routine activities theory and social disorganization theory and provides a logical framework for understanding the connections between neighborhood context and micro-spatial environmental conditions.